2014
DOI: 10.5430/jnep.v4n5p64
|View full text |Cite
|
Sign up to set email alerts
|

Tensions during a process of change – implementation of the Bologna educational reform in Swedish specialist nursing programmes

Abstract: Background/Objective: This study is an enquiry into the process of change during the implementation of the European educational reform, the Bologna process. The aim was to critically elaborate tensions during the process, focusing on the implementation of the degree project into Swedish specialist nursing programmes.Methods: Data were collected in a multi-centre participatory research project during the period August 2007 to January 2011, and consisted of memorandums kept by the project members and written vig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Health care has a strong framework of regulations and traditions but introducing new ways of collaboration in a research context may contribute to both theory development and clinical development, something that has been done successfully in other areas of participatory research but not found in the development of health care materials. The same research reveals issues similar to those we have found, namely that action research is time-consuming (Linden et al, 2012), staff are insecure about viewing patients as capable (Bengtsson, Kasperowski, Ring, & Kjellgren, 2014) and shared involvement is possible between stakeholders through synthesizing conflicting views (Berg et al, 2014). This needs to be addressed and further researched.…”
Section: Discussionsupporting
confidence: 62%
“…Health care has a strong framework of regulations and traditions but introducing new ways of collaboration in a research context may contribute to both theory development and clinical development, something that has been done successfully in other areas of participatory research but not found in the development of health care materials. The same research reveals issues similar to those we have found, namely that action research is time-consuming (Linden et al, 2012), staff are insecure about viewing patients as capable (Bengtsson, Kasperowski, Ring, & Kjellgren, 2014) and shared involvement is possible between stakeholders through synthesizing conflicting views (Berg et al, 2014). This needs to be addressed and further researched.…”
Section: Discussionsupporting
confidence: 62%
“…13 Development of clinicians as faculty included offering a three-credit curriculum development course at the VA. Efforts to use theory and research evidence to drive project initiatives weren't always warmly received.…”
Section: Stormingmentioning
confidence: 99%